Proposed Integrated Marketing Communication of TELKOM FLEXI to Improve ITS Marketing Communication Effectiveness - Puspita, Fitri; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2013)
PT Telkom facing a business issue where their new user and ARPU (average revenue per user) target for Flexi in 2011 was not achieved and despite having the biggest market share among CDMA operators, but in fact, Flexi’s brand value was below its main competitor. There are several factors that cause this issue; one of them is marketing communication that became the focus of this final project. Researcher used the theory of integrated marketing communication (IMC), particularly regarding the effectiveness of an integrated marketing communication, evaluation of the integration of all marketing communications components, and marketing communications planning. The data were collected through a survey of Flexi users and non-users as well as interviews with Flexi sales manager assistant. The results showed that the cause of the issue is ineffective marketing communication integration due to ineffective marketing communication channels and inefficient marketing budget allocations. The solutions of the problem are new marketing communication that integrated with marketing objectives, customer behaviors, and marketing communication’s budget allocation. Therefore, the researcher recommends Flexi to use direct from Telkom, TV and internet to provide information about Flexi’s features. Utilize TV, outdoor advertising, and print to increase the purchase intention. Make a new MC budget allocation plan by increasing the budget for internet, print, TV, outdoor advertising and bank channels and decreasing the budget allocation for radio, outlet, sales agency, trade showbooth, and event sponsorship channels. Keywords: Integrated Marketing Communication, Marketing Communication Effectiveness, Marketing Communication Budgeting, IMC Planning